KARAKTERISTIK PERUSAHAAN DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN OTOMOTIF - Sugeng Haryanto (Jurnal Keuangan dan Perbankan, 2012)
The company financial management should be able to meet the needs of the funds that would be used to operateor expand their businesses. Financing the use of corporate funds was faced to a choice: debt or raise capital withthe level of consequence risk of each. Consideration of a company was choosing the source of funds in anefficient and profitable enterprise for both current and for the foreseeable future. It considered that the choice ofthe source of the funds would have an impact on corporate performance in the future, namely funding responsibilityof the company. The objective of this study was to analyze the influence of company characteristics andbusiness risk significantly influenced capital structure, to determine the effect of the variable characteristics ofcompanies and business risk simultaneously on the companys capital structure, to determine the variables ofcompany characteristics and business risk simultaneously toward the company capital structure, to know thevariables that had most dominant impact toward capital structure. The results of the analysis showed theintensity of DOL assets, sales growth, profitability (ROA) affected the companys capital structure, while thevariable of ROA had dominant contribution. Free variables simultaneously affected the capital structure.